Design and Analysis of A Parallelized Electrically Controlled Droplet Generating Device - ZHU, CHAO (My University, 2013)
Microdroplets find use in a variety of applications ranging from chemical synthesis to biological analysis. However, commercial use of microdroplets has been stymied in many applications, as current devices lack one or more of the critical features such as precise and dynamic control of the droplet size, high throughput and easy fabrication. This work involves design, fabrication and characterization of a microdroplet generating device that uses low cost fabrication, allows dynamic control of the droplet size and achieves parallelized droplet generation for high throughput.
Dynamic droplet size control by DC electric field has been demonstrated with the device. By varying the potential from 300 V to 1000 V, the droplet size can change from 140 microns to around 40 microns . The transition of the droplet size just takes few seconds. Parallelized droplet generation has also been demonstrated. The standard deviation of the droplet size is lower than 4% for the three-capillary device and lower than 6% for the five-capillary device under different operating conditions. Highest throughput of 0.75 mL/hour is achieved on the five-capillary device. It has been show that this proposed device has a better performance than the existing PDMS based parallel droplet generating devices. A theoretical model of the droplet generating process has also been developed which is able to predict the droplet size at various potentials. The theoretical results are in good agreement with experimental ones.
Keywords: Microfluidics; Droplet Generation; Electrically Control; Parallelization; Other Mechanical Engineering; Other Mechanical Engineering